Diseños tipos de Áreas de infiltración para vertidos de biodigestores en subsuelos frecuentes de la Sierra Ecuatoriana - León Cerón, Katherine Alejandra (2021)
In Ecuador, only 53% of the population has a sewer service. Among the provinces with the most significant coverage is Pichincha, followed by Carchi, Imbabura, Tungurahua, El Oro, and Azuay. The provinces with the lowest percentage of coverage are Los Rios, Galápagos, Orellana, and Bolívar, with values lower than 40%. Access to sewerage in rural areas is deficient, and due to its need, users evacuate sewage to wells and septic tanks. In most cases, the process is carried out empirically without taking into account necessary factors, such as carrying out a previous soil study to find out its characteristics. The lack of consideration of an infiltration area after the septic tank generates an inadequate evacuation of the water, contamination, and putrid odors. Civil engineers who design or build septic tanks must carry out the preliminary study to know the soils' infiltration speed where sewage is discharged. In 2020 Chafla carried out the compilation of in situ investigations of undergraduate students of the UNACH obtaining. As a result, a statistical analysis of the velocities associated with soil types A2 and A3. Those that present sufficient data to determine mathematical relationships that allow predicting the infiltration speed. In this research, the calculation of the infiltration area for discharges of biodigesters for type A2 A3 soils is carried out using three different filtering materials such as sand, gravel, and ball stone